Acute focal bacterial nephritis developed in a healthy child - Alaygut, Demet; Bayram, Meral; Soylu, Alper; Türkmen, Mehmet; Kavukçu, Salih (The Turkish Journal of Pediatrics, 2013)
Acute focal bacterial nephritis (AFBN) is a rare cause of interstitial bacterial nephritis. Ultrasound identifies AFBN as a hypoechogenic and hypoperfused parenchymal lesion, which requires its differentiation from renal abscess and tumor. Hematogenous spread or ascending infection arising from the lower urinary tract is thought to be involved in the pathogenesis of AFBN. Herein, a six-year-old healthy male patient, diagnosed using ultrasound and computerized tomography (CT) and treated with intravenous antibiotics, is presented. As a result, AFBN can be seen in healthy children without any history of reflux or urinary tract infection, and differentiation from renal abscess is important.